The Influence of Price on Consumer Purchase Interest at Nusa Dua Beach Hotel & Spa - Paramarta, Kadek Yoga; Suastini, Ni Made; Adinda, Clearesta (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
The hotel implements strategies to increase consumer purchasing interest, one of which is through an optimal pricing policy. The purpose of this study is to analyze the effect of price on consumer purchasing interest. This study was conducted at Nusa Dua Beach Hotel & Spa, Bali, with a population of 97 tourists who had visited the official website of Nusa Dua Beach Hotel & Spa but had never stayed there. This study utilized primary data in the form of a questionnaire (questionnaire) filled out by the respondents and returned to the researcher. The sampling method in this study was to implement the incidental sampling technique. The analysis method used simple linear regression with SPSS version 25 for Windows. This study shows the results that the Price variable (X) has a significant effect on Purchase Interest (Y) with a calculated t value> t table = 16.103> 1.661 and a significance value <α = 0.000 <0.05. It can be interpreted that this study shows the results that price has a positive and significant effect on Purchase Interest at Nusa Dua Beach Hotel & Spa.